Strong-acidity FAU type molecular sieve and preparation method thereof
By doping Zr into the skeleton of the FAU molecular sieve and performing homocrystal substitution reaction with gas-phase SiCl4, the problem of increasing the strong acidity content of FAU molecular sieve is solved, and the combination of high silicon-rhenium ratio and high crystallinity is achieved, simplifying the production process and reducing costs.
Patent Information
- Application Number
- CN202311203470.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-09-18
AI Technical Summary
The prior art is difficult to greatly increase the strong acid content of FAU molecular sieve under the conditions of ensuring high crystallinity and high silicon-aluminum ratio, especially in catalyst applications, there are problems such as catalyst carbon deposits, low selectivity and short life.
By doping Zr elements into the skeleton of the FAU-type molecular sieve and performing homocrystal substitution reaction with gas-phase SiCl4, a significant increase in the strong acidity content of the FAU-type molecular sieve is achieved, while increasing the silicon-aluminum ratio and retaining high crystallinity.
The strong acid content of FAU-type molecular sieve has been significantly improved, the silicon-aluminum ratio has been greatly improved, the crystallinity remains above 80%, and multiple ammonium ion exchanges and hydrothermal treatments have been avoided, which simplifies the production process and reduces costs.
Smart Images

Figure BDA0004456243320000121 
Figure BDA0004456243320000131 
Figure HDA0004456243330000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of molecular sieve preparation, and in particular relates to a strongly acidic FAU type molecular sieve and a preparation method thereof. Background Art
[0002] FAU molecular sieves have a three-dimensional smooth skeleton structure, a relatively high specific surface area, adjustable pore size and acidity, and excellent thermal and hydrothermal stability. They are widely used in petroleum refining and chemical industries, especially in fluidized bed catalytic cracking and catalytic cracking reactions. At the same time, FAU molecular sieves also show excellent performance in the adsorption of organic volatiles. However, there are many substantial problems in the specific application of direct catalytic cracking of crude oil to produce light olefins, such as serious carbon deposition of the catalyst, low selectivity for light olefin products, short catalyst life, the need to adjust the acidity, and low catalyst activity. In order to further improve the catalytic performance of FAU molecular sieves and their application value in actual production processes, researchers generally modify the molecular sieves to meet the requirements of use. Among them, the acidity adjustment of FAU type molecular sieves, especially the increase of strong acid content, is of great significance to improving the catalytic performance of FAU type molecular sieves. However, the existing modification methods for FAU type molecular sieves are difficult to achieve an effective increase in the strong acid content, especially it is difficult to achieve an effective increase in the strong acid content while taking into account a high silicon-aluminum ratio and a high crystallinity.
[0003] Based on this, at present, there is still a need to study simple and easy-to-implement technical solutions that can significantly increase the strong acid content of FAU type molecular sieves while ensuring high crystallinity and high silicon-to-aluminum ratio. Summary of the invention
[0004] The object of the present invention is to provide a technical solution that can significantly increase the strong acid content of FAU type molecular sieves; the FAU type molecular sieve prepared by the technical solution has high crystallinity and high framework silicon-aluminum ratio while having high strong acid content.
[0005] In order to achieve the above objectives, the present invention provides the following two technical solutions.
[0006] In a first aspect, the present invention provides a method for preparing a strongly acidic FAU type molecular sieve, wherein the method comprises:
[0007] A FAU type molecular sieve containing the metal element Zr in the framework is subjected to isomorphous substitution reaction with gas phase SiCl4 at a mass ratio of 0.1-20:1, and then calcined to obtain a high silicon-aluminum ratio FAU type molecular sieve;
[0008] Wherein, the reaction temperature of the isomorphous substitution reaction is 200-600°C;
[0009] Among them, the molar ratio of ZrO2 to Al2O3 in the FAU type molecular sieve containing the metal element Zr in the framework is 0.01-10.0.
[0010] The technical solution provided by the present invention is to first dope Zr into the FAU type molecular sieve framework, and then cooperate with gas phase SiCl4 to carry out isomorphous substitution reaction, so as to realize a substantial increase in the strong acid content of the FAU type molecular sieve while realizing a substantial increase in the silicon-aluminum ratio and retaining a high degree of crystallinity. The strongly acidic FAU type molecular sieve obtained by the technical solution provided by the present invention is a strongly acidic FAU type molecular sieve containing heteroatom Zr in the framework. In the technical solution provided by the present invention, Zr atoms are first doped into the FAU type molecular sieve framework to enter the molecular sieve framework to replace the position of a small part of the Al atoms in the FAU type molecular sieve framework, and then gas phase SiCl4 is carried out for isomorphous substitution reaction, and gas phase SiCl4 and the FAU type molecular sieve framework heteroatom Zr further synergize to isomorphously replace Al atoms, so that the strong acid content is greatly improved, the silicon-aluminum ratio is greatly improved, and the prepared FAU type molecular sieve has high relative crystallinity.
[0011] According to a preferred embodiment of the first aspect, the method further comprises the step of preparing a FAU type molecular sieve containing the metal element Zr in the framework, specifically comprising:
[0012] Sodium hydroxide, an aluminum source, a silicon source and water are mixed in a molar ratio of (10-30)Na2O:Al2O3:(10-30)SiO2:(180-400)H2O, and aged at 0-80°C to obtain a directing agent;
[0013] A directing agent, sodium hydroxide, a silicon source, an aluminum source, a zirconium source and water are mixed according to a molar ratio of (1-10) Na2O: Al2O3: (0.01-10.0) ZrO2: (5-20) SiO2: (120-360) H2O to obtain a reaction system to be crystallized, and the reaction system to be crystallized at 60-120° C. to obtain a FAU type molecular sieve containing the metal element Zr in the framework; wherein, based on the mass of Al2O3 in the reaction system to be crystallized as 100%, the mass of Al2O3 provided by the directing agent accounts for 3-25% of the mass of Al2O3 in the reaction system to be crystallized;
[0014] The preferred technical solution is to introduce Zr heteroatoms into the framework of the molecular sieve by a direct synthesis method, and then the obtained FAU molecular sieve containing Zr heteroatoms is subjected to isomorphous substitution reaction with gas phase SiCl4 at a certain temperature, and then roasted to obtain a strong acid FAU molecular sieve with a framework containing Zr heteroatoms; the FAU molecular sieve prepared by this method not only has a high strong acid content but also has a high crystallinity and a high silicon-to-aluminum ratio, and does not require multiple ammonium ion exchange and hydrothermal treatment processes, so that the sodium oxide content of the molecular sieve can be reduced to below 1.0wt%; compared with the FAU molecular sieve prepared by the preferred technical solution using the traditional metal impregnation and hydrothermal ultra-stabilization technology, the FAU molecular sieve has a higher strong acid content, a higher silicon-to-aluminum ratio and a higher crystallinity, and no ammonium ion exchange and hydrothermal treatment processes are required during the preparation process, thereby shortening the production process, reducing production costs, and reducing ammonia nitrogen wastewater discharge, etc.;
[0015] The preferred technical solution is to introduce Zr heteroatoms into the framework of the molecular sieve by a direct synthesis method (in the process of molecular sieve synthesis, a metal Zr source is directly added to the synthesis gel and then crystallized to introduce metal Zr into the framework of the molecular sieve). Compared with the traditional impregnation method or ion exchange method, it has significant advantages: the introduction of Zr heteroatoms by impregnation method or ion exchange method is easy to block the structure and pores of the molecular sieve, and the structure between the Zr component and the molecular sieve is not strong enough. In actual use, due to the frequent impact and thermal vibration of the high air velocity gas flow, the Zr component is easy to fall off, which not only causes the loss of effective ingredients, but also shortens the service life of the catalyst; while the introduction of Zr heteroatoms into the framework of the molecular sieve by the direct synthesis method can effectively reduce the loss of Zr components in actual use, and is more conducive to the adjustment of the acid properties and pore structure and other physical and chemical properties of the molecular sieve to different degrees, and is more conducive to the application of the molecular sieve in shape selection and acid catalysis;
[0016] Furthermore, the molar ratio of ZrO2 to Al2O3 in the FAU type molecular sieve containing the metal element Zr in the framework is 0.05-3.0.
[0017] Further, in the process of preparing the directing agent, sodium hydroxide, an aluminum source, a silicon source and water are mixed in a molar ratio of (10-20)Na2O:Al2O3:(10-20)SiO2:(240-360)H2O;
[0018] Furthermore, in the process of preparing the reaction system to be crystallized, the directing agent, sodium hydroxide, silicon source, aluminum source, zirconium source and water are mixed according to the molar ratio of (1-5) Na2O:Al2O3:(0.01-5.0) ZrO2:(5-15) SiO2:(150-300) H2O to obtain the reaction system to be crystallized (gel mixture), and the reaction system to be crystallized is crystallized at 60-120°C.
[0019] Further, in the process of preparing the directing agent, the directing agent is aged at 10-60° C. to obtain the directing agent;
[0020] Further, the aging time is 1-60h; further, the aging time is 2-50h;
[0021] Further, the crystallization is carried out at 70-110°C;
[0022] Further, the crystallization time is 0.5-72h; further, the crystallization time is 12-48h;
[0023] Furthermore, the crystallized sample is filtered, washed and dried; further, the drying is performed at 120° C. for 24 hours.
[0024] Furthermore, the silicon source includes but is not limited to at least one of ethyl silicate, water glass and silica sol.
[0025] Further, the aluminum source includes but is not limited to at least one of sodium metaaluminate, aluminum sulfate, aluminum isopropoxide, tert-butyl aluminum and aluminum oxide;
[0026] Furthermore, the zirconium source includes but is not limited to at least one of zirconium chloride, zirconium sulfate, and zirconium oxychloride.
[0027] According to a preferred embodiment of the first aspect, when the isomorphous substitution reaction is carried out, the mass ratio of the FAU type molecular sieve containing the metal element Zr in the framework to the gas phase SiCl4 is 0.5-10:1.
[0028] According to a preferred embodiment of the first aspect, the reaction temperature of the isomorphous substitution reaction is 280-580°C.
[0029] According to a preferred embodiment of the first aspect, the reaction time of the isomorphous substitution reaction is 10 minutes to 5 hours.
[0030] According to a preferred embodiment of the first aspect, the method further comprises cooling, washing, filtering and drying the isomorphous substitution reaction product after the isomorphous substitution reaction and before calcination;
[0031] Furthermore, the cooling is carried out under N2 purge.
[0032] According to a preferred embodiment of the first aspect, the calcination temperature is 500-600°C.
[0033] According to a preferred embodiment of the first aspect, the calcination time is 2-6 hours.
[0034] In a second aspect, the present invention provides a strongly acidic FAU type molecular sieve prepared by the preparation method of the strongly acidic FAU type molecular sieve provided in the first aspect;
[0035] The strong acid FAU type molecular sieve contains heteroatom Zr in the framework, the proportion of strong acid in the total acid is more than 40%, the framework silicon-aluminum molar ratio n(SiO2) / n(Al2O3) is more than 6, and the relative crystallinity is more than 80%.
[0036] Since metal heteroatoms are different from Si and Al atoms in the molecular sieve framework in terms of ionic radius, electronegativity and complexing ability, the introduction of metal heteroatoms will regulate the acidity and surface properties of the molecular sieve catalyst. However, due to the diversity of heteroatom types and the diversity of molecular sieve pores, the effects of different heteroatoms on the performance of different molecular sieves are different. Therefore, what kind of heteroatom will be introduced into what kind of molecular sieve and what kind of performance impact has always been a research difficulty in the field of molecular sieves. The present invention achieves a substantial improvement in FAU type molecular sieves by introducing Zr atoms into the FAU type molecular sieve framework and then performing an isomorphous substitution reaction with SiCl4. Compared with the prior art, it has the following beneficial effects:
[0037] 1. The technical solution provided by the present invention achieves a significant increase in the strong acid content of the FAU type molecular sieve by isomorphously replacing the FAU type molecular sieve containing the metal element Zr in the framework with gas phase SiCl4 and then calcining it. The proportion of strong acid in the obtained FAU type molecular sieve is more than 40%.
[0038] 2. The technical solution provided by the present invention achieves a significant increase in the framework silicon-to-aluminum ratio of the FAU type molecular sieve by isomorphously replacing the FAU type molecular sieve containing the metal element Zr in the framework with gas-phase SiCl4 and then calcining. The framework silicon-to-aluminum molar ratio n(SiO2) / n(Al2O3) of the prepared FAU type molecular sieve is above 6.
[0039] The technical solution provided by the present invention can obtain FAU type molecular sieves with different silicon-to-aluminum ratios by regulating the reaction conditions of FAU type molecular sieves containing the metal element Zr in the framework and gas phase SiCl4. In the preferred technical solution, the framework silicon-to-aluminum molar ratio n(SiO2) / n(Al2O3) of the FAU type molecular sieve can reach more than 17 or even more than 20.
[0040] 3. The FAU molecular sieve prepared by the technical solution provided by the present invention has strong acidity, a high framework silicon-aluminum ratio and a high crystallinity, with a crystallinity of more than 80%.
[0041] 4. The technical solution provided by the present invention is to obtain a FAU type molecular sieve with strong acidity, high silicon-aluminum ratio and high crystallinity by isomorphous substitution of a FAU type molecular sieve containing the metal element Zr in the framework with gas-phase SiCl4 and then calcining. There is no need for multiple ammonium ion exchanges and harsh hydrothermal treatments (600°C-700°C) to reduce the sodium oxide content of the FAU type molecular sieve to below 1.0wt%. The production process is simple, the production cost is low, and the discharge of ammonia nitrogen wastewater is reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 XRD spectra of the molecular sieves provided in Examples 1 to 5.
[0043] Figure 2 XRD spectra of the molecular sieves provided for Comparative Examples 1 to 3. DETAILED DESCRIPTION
[0044] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0045] The relative crystallinity, unit cell parameters and framework silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of the molecular sieve in the present invention are determined by X-ray diffraction (XRD), and the spectrum with a 2θ angle of 5 to 40° is recorded. The metal element content and Na2O content of the molecular sieve are measured by an X-ray fluorescence spectrometer, the specific surface area and pore structure parameters are measured by low-temperature nitrogen adsorption and desorption, and the proportion of strong acid content to total acid content is measured by a chemical adsorption instrument NH3-TPD.
[0046] Sodium hydroxide: produced by Beijing Chemical Plant, purity is 99%;
[0047] Sodium aluminate: produced by Tianjin Jinke Fine Chemical Research Institute, Al2O3 content is 45wt%, Na2O content is 41wt%, and the balance is water;
[0048] Water glass: produced by Beijing Red Star Soda Factory, with SiO2 content of 28.83wt%, Na2O content of 8.84wt%, and the balance being water;
[0049] Silica sol: produced by Tianjin Jinke Fine Chemical Research Institute, SiO2 content is 28.88wt%, the balance is water;
[0050] Aluminum sulfate: produced by Nanzhao Huaxin Chemical Co., Ltd., with a purity of 99%;
[0051] Zirconium nitrate (ZrNO3·5H2O): Produced by Beijing Chemical Plant, purity 99%.
[0052] Zirconium chloride (ZrCl4): Produced by Tianjin Jinke Fine Chemical Research Institute, purity 99%.
[0053] Zirconium oxychloride (ZrOCl2·8H2O): Produced by Tianjin Jinke Fine Chemical Research Institute, with a purity of 99%.
[0054] Ammonium chloride: Produced by Beijing Chemical Plant, purity is 99%.
[0055] Aluminum isopropoxide: Shanghai MacLean Biochemical Technology Co., Ltd., purity 99.8%;
[0056] Alumina: Shanghai MacLean Biochemical Technology Co., Ltd., purity 99.99%;
[0057] Ethyl silicate: Shanghai MacLean Biochemical Technology Co., Ltd., SiO2 content is 28.83wt%, the balance is water.
[0058] Example 1
[0059] This embodiment provides a strongly acidic FAU type molecular sieve, which is prepared by the following preparation method:
[0060] 37.09 g of silica sol, 15.48 g of sodium hydroxide, 3.06 g of sodium aluminate and 44.38 g of distilled water were mixed at 50° C. and stirred for 30 min to mix evenly, and then aged at 40° C. for 4 h to obtain a directing agent.
[0061] 20.27 g NaOH and 79.70 g distilled water were added to 132.47 g silica sol, and the mixture was stirred for 30 min to be uniformly mixed. Then, 80 g of a directing agent was added, and after stirring for 1 h, 1.58 g of sodium aluminate and 81.54 g of distilled water were added, and after stirring for 1 h, 98.72 g of aluminum sulfate solution (with an Al2O3 mass concentration of 7.6 wt%) was added, and after stirring for 1 h, 10.8 g of zirconium nitrate (ZrNO3·5H2O) was added, and stirring was continued for 1 h to obtain a reaction system to be crystallized; the reaction system to be crystallized was placed in a stainless steel The product was placed in a steel crystallization kettle, sealed, and subjected to dynamic crystallization in a rotary oven at 95°C for 32 hours. The product was then filtered, washed, and the filter cake was dried in an oven at 120°C for 24 hours. The dried product was transferred to a quartz tube reactor of a rotary tube furnace, purged with high-purity nitrogen, and programmed to rise in temperature (4° / min) to 550°C. The product was calcined at 550°C for 4 hours to obtain a FAU type molecular sieve containing the metal element Zr in the framework (the molar ratio of ZrO2 to Al2O3 is 0.26).
[0062] Then, 8.61 g of gaseous SiCl4 was introduced into a quartz tube reactor of a rotary tube furnace containing 50 g of a FAU type molecular sieve containing the metal element Zr in the framework to carry out an isomorphous substitution reaction at 380°C for 1 hour. The product of the isomorphous substitution reaction was repeatedly washed with deionized water, filtered, dried, and calcined at 550°C in a nitrogen atmosphere for 4 hours to obtain a FAU type molecular sieve containing the metal element Zr, named Zr-FAU-1-isomorphous substitution. The physicochemical property data of the sample are shown in Table 1, and the XRD spectrum is shown in Figure 1 .
[0063] Example 2
[0064] This embodiment provides a strongly acidic FAU type molecular sieve, which is prepared by the following preparation method:
[0065] 38.58 g of ethyl silicate, 15.48 g of sodium hydroxide, 70 g of distilled water and 3.06 g of sodium aluminate were mixed at 30° C. and stirred for 1 h, and then aged at 30° C. for 6 h to obtain a directing agent.
[0066] 23.27 g NaOH and 182.43 g distilled water were added to 137.79 g ethyl silicate and stirred for 1 h to mix evenly, then 100 g directing agent was added and stirred for 1 h, 1.58 g sodium aluminate was dissolved in 101.54 g distilled water and added to the above solution and stirred for 1 h, 1.11 g aluminum isopropoxide was dissolved in 92 g water and added to the mixed solution and stirred for 1 h, then 12.8 g zirconium nitrate (ZrNO3·5H2O) was added and stirred for 1 h to obtain a reaction system to be crystallized; The reaction system to be crystallized is placed in a stainless steel crystallization kettle, sealed and dynamically crystallized in a rotary oven at 100°C for 28 hours, filtered, washed, and the filter cake is dried in an oven at 120°C for 24 hours; the dried product is transferred to a quartz tube reactor of a rotary tube furnace, purged with high-purity nitrogen, and programmed to heat (4° / min) to 550°C, and calcined at 550°C in a nitrogen atmosphere for 4 hours. The FAU type molecular sieve containing the metal element Zr (the molar ratio of ZrO2 to Al2O3 is 1.11) is obtained.
[0067] Then, 7.78 g of gaseous SiCl4 was introduced into a quartz tube reactor of a rotary tube furnace containing 25 g of FAU molecular sieve containing the metal element Zr in the framework to carry out isomorphous substitution reaction at 410°C for 1 hour. Then, the product of the isomorphous substitution reaction was repeatedly washed with deionized water, filtered, dried, and calcined at 550°C for 4 hours to obtain a strongly acidic FAU molecular sieve named Zr-FAU-2-isomorphous substitution. The physicochemical properties of the sample are shown in Table 1, and the XRD spectrum is shown in Figure 1 .
[0068] Comparative Example 1
[0069] This comparative example provides a Y-type molecular sieve, which is prepared by a conventional hydrothermal USY-type molecular sieve preparation method, specifically:
[0070] 38.58 g of ethyl silicate, 15.48 g of sodium hydroxide, 70 g of distilled water and 3.06 g of sodium aluminate were mixed at 30° C. and stirred for 1 h, and then aged at 30° C. for 6 h to obtain a directing agent.
[0071] 23.27 g NaOH and 182.43 g distilled water were added to 137.79 g ethyl silicate and stirred for 1 h to mix evenly, then 100 g directing agent was added and stirred for 1 h, 1.58 g sodium aluminate was dissolved in 101.54 g distilled water and added to the above solution, stirred for 1 h, 1.11 g aluminum isopropoxide was dissolved in 92 g water and added to the mixed solution, stirred for 1 h, and then stirred for 1 h to obtain a reaction system to be crystallized; the reaction system to be crystallized was placed in a stainless steel crystallization kettle, sealed in a 100 ° C oven in a rotary oven for dynamic crystallization for 28 h, filtered, washed, and the filter cake was dried in a 120 ° C oven for 24 h; the dried product was transferred to a quartz tube reactor of a rotary tube furnace, purged with high-purity nitrogen, and programmed to heat (4 ° / min) to 550 ° C, and calcined at 550 ° C in a nitrogen atmosphere for 4 h to obtain a NaY type molecular sieve.
[0072] The NaY molecular sieve was mixed with an ammonium chloride solution with a concentration of 1 mol / L in a mass ratio of 1:10 and ion exchanged at 90°C for 1 hour, filtered, washed repeatedly, and the filter cake was dried in an oven at 120°C for 24 hours, and then treated with 100% water vapor at 600°C for 2 hours. The above steps were repeated for another ion exchange and water vapor treatment to obtain a hydrothermal USY molecular sieve named USY-1. The physicochemical properties of the sample are shown in Table 1, and the XRD spectrum is shown in Figure 2 .
[0073] Comparative Example 2
[0074] This comparative example provides a Y-type molecular sieve, which is prepared by the following preparation method:
[0075] 38.58 g of ethyl silicate, 15.48 g of sodium hydroxide, 70 g of distilled water and 3.06 g of sodium aluminate were mixed at 30° C. and stirred for 1 h, and then aged at 30° C. for 6 h to obtain a directing agent.
[0076] 23.27 g of NaOH and 182.43 g of distilled water were added to 137.79 g of ethyl silicate and stirred for 1 hour to mix evenly, then 100 g of directing agent was added and stirred for 1 hour, 1.58 g of sodium aluminate was dissolved in 101.54 g of distilled water and added to the above solution and stirred for 1 hour, 1.11 g of aluminum isopropoxide was dissolved in 92 g of water and added to the mixed solution and stirred for 1 hour to form a gel mixture, and the mixture was stirred for 1 hour to obtain a reaction system to be crystallized; the reaction system to be crystallized was added to the reaction system to be crystallized. The system was placed in a stainless steel crystallization kettle, sealed and placed in a rotary oven at 100°C for dynamic crystallization for 28 hours, filtered, washed, and the filter cake was dried in a 120°C oven for 24 hours; the dried product was transferred to a quartz tube reactor of a rotary tube furnace, purged with high-purity nitrogen, and programmed to rise in temperature (4° / min) to 550°C, and calcined at 550°C in a nitrogen atmosphere for 4 hours to obtain a NaY type molecular sieve, named NaY-1. The physicochemical properties of the sample are shown in Table 1.
[0077] The NaY molecular sieve was mixed with an ammonium chloride solution with a concentration of 1 mol / L at a mass ratio of 1:10 and ion exchange was carried out at 90°C for 1 hour, filtered, washed repeatedly, and the filter cake was dried in an oven at 120°C for 24 hours; the above steps were repeated for another ion exchange to obtain a HY molecular sieve, named HY-1. The physicochemical properties of the sample are shown in Table 1.
[0078] Comparative Example 3
[0079] This comparative example provides a FAU type molecular sieve, which is prepared by the following preparation method:
[0080] 38.58 g of ethyl silicate, 15.48 g of sodium hydroxide, 70 g of distilled water and 3.06 g of sodium aluminate were mixed at 30° C. and stirred for 1 h, and then aged at 30° C. for 6 h to obtain a directing agent.
[0081] 23.27 g NaOH and 182.43 g distilled water were added to 137.79 g ethyl silicate and stirred for 1 h to mix evenly, then 100 g directing agent was added and stirred for 1 h, 1.58 g sodium aluminate was dissolved in 101.54 g distilled water and added to the above solution and stirred for 1 h, 1.11 g aluminum isopropoxide was dissolved in 92 g water and added to the mixed solution and stirred for 1 h, then 12.8 g zirconium nitrate (ZrNO3·5H2O) was added and stirred for 1 h to obtain a reaction system to be crystallized; The reaction system to be crystallized is placed in a stainless steel crystallization kettle, sealed and dynamically crystallized in a rotary oven at 100°C for 28 hours, filtered, washed, and the filter cake is dried in an oven at 120°C for 24 hours; the dried product is transferred to a quartz tube reactor of a rotary tube furnace, purged with high-purity nitrogen, and programmed to heat (4° / min) to 550°C, and calcined at 550°C in a nitrogen atmosphere for 4 hours. The FAU type molecular sieve containing the metal element Zr (the molar ratio of ZrO2 to Al2O3 is 1.11) is obtained.
[0082] The FAU molecular sieve containing the metal element Zr in the framework was mixed with an ammonium chloride solution with a concentration of 1 mol / L at a mass ratio of 1:10, and ion exchange was performed at 90°C for 1 hour, filtered, washed repeatedly, and the filter cake was dried in an oven at 120°C for 24 hours, and then treated with 100% water vapor at 600°C for 2 hours. The above steps were repeated for another ion exchange and a water vapor treatment to obtain a hydrothermal FAU molecular sieve containing heteroatom Zr, named Zr-FAU-hydrothermal. The physicochemical property data of the sample are shown in Table 1, and the XRD spectrum is shown in Figure 2 .
[0083] Comparative Example 4
[0084] This comparative example provides a FAU type molecular sieve, which is prepared by the following method:
[0085] 38.58 g of ethyl silicate, 15.48 g of sodium hydroxide, 70 g of distilled water and 3.06 g of sodium aluminate were mixed at 30° C. and stirred for 1 h, and then aged at 30° C. for 6 h to obtain a directing agent.
[0086] 23.27 g NaOH and 182.43 g distilled water were added to 137.79 g ethyl silicate, stirred for 1 h to mix evenly, then 100 g directing agent was added, stirred for 1 h, 1.58 g sodium aluminate was dissolved in 101.54 g distilled water and added to the above solution, stirred for 1 h, 1.11 g aluminum isopropoxide was dissolved in 92 g water and added to the mixed solution, stirred for 1 h, 12.8 g zirconium nitrate (ZrNO3·5H2O) was added, and stirring was continued for 1 h to obtain a reaction system to be crystallized; the reaction system to be crystallized was placed in a stainless steel crystallization kettle. , sealed in a 100°C oven and subjected to dynamic crystallization for 28 hours in a rotary oven, filtered, washed, and the filter cake was dried in a 120°C oven for 24 hours; the dried product was transferred to a quartz tube reactor of a rotary tube furnace, purged with high-purity nitrogen, and programmed to rise in temperature (4° / min) to 550°C, and calcined at 550°C in a nitrogen atmosphere for 4 hours. The FAU type molecular sieve containing the metal element Zr (the molar ratio of ZrO2 to Al2O3 is 1.11) is named Zr-Na-FAU-without isomorphous substitution. The physicochemical properties of the sample are shown in Table 1.
[0087] The molecular sieve Zr-Na-FAU-unisomorphously substituted was mixed with an ammonium chloride solution with a concentration of 1 mol / L at a mass ratio of 1:10 and ion exchange was carried out at 90°C for 1 hour, filtered, washed repeatedly, and the filter cake was dried in an oven at 120°C for 24 hours; the above steps were repeated for another ion exchange to obtain an H-type molecular sieve, named Zr-H-FAU-unisomorphously substituted. The physicochemical property data of the sample are shown in Table 1.
[0088] Comparative Example 5
[0089] This comparative example provides a Y-type molecular sieve, which is prepared by the following method:
[0090] 38.58 g of ethyl silicate, 15.48 g of sodium hydroxide, 70 g of distilled water and 3.06 g of sodium aluminate were mixed at 30° C. and stirred for 1 h, and then aged at 30° C. for 6 h to obtain a directing agent.
[0091] 23.27 g NaOH and 182.43 g distilled water were added to 137.79 g ethyl silicate and stirred for 1 h to mix evenly. Then 100 g directing agent was added and stirred for 1 h. 1.58 g sodium aluminate was dissolved in 101.54 g distilled water and added to the above solution and stirred for 1 h. 1.11 g aluminum isopropoxide was dissolved in 92 g water and added to the mixed solution and stirred for 1 h. The mixture was stirred for 1 h and then stirred for 1 h to obtain a reaction system to be crystallized (the molar ratio of the components of the gel mixture was Na2O:Al2O3:S iO2:H2O=3:1:9:232); the reaction system to be crystallized is placed in a stainless steel crystallization kettle, sealed and placed in a rotary oven at 100°C for dynamic crystallization for 28 hours, filtered, washed, and the filter cake is dried in an oven at 120°C for 24 hours; the dried product is transferred to a quartz tube reactor of a rotary tube furnace, purged with high-purity nitrogen, and programmed to heat (4° / min) to 550°C, and calcined at 550°C in a nitrogen atmosphere for 4 hours to obtain a NaY type molecular sieve free of heteroatom Zr.
[0092] Then, 7.78 g of gaseous SiCl4 was introduced into a quartz tube reactor of a rotary tube furnace containing a NaY type molecular sieve without heteroatom Zr to carry out an isomorphous substitution reaction at 350°C for 1 hour. The product of the isomorphous substitution reaction was repeatedly washed with deionized water, filtered, dried, and calcined at 550°C for 4 hours to obtain a FAU type molecular sieve without heteroatom Zr, named FAU-2-without Zr. The physicochemical properties of the sample are shown in Table 1, and the XRD spectrum is shown in Figure 2 .
[0093] Comparative Example 6
[0094] This comparative example provides a FAU type molecular sieve, which is prepared by the following method:
[0095] 2.22 g of sodium aluminate, 8.21 g of sodium hydroxide, 35.62 g of distilled water, and 30.61 g of water glass were mixed in order, stirred evenly, and aged at 25° C. for 24 hours to obtain a directing agent.
[0096] 188.7 g of water glass, 46.3 g of 30 wt% sodium aluminate solution, 42.8 g of 50 wt% aluminum sulfate solution, 3.99 g of zirconium nitrate and 40.3 g of a directing agent were mixed and stirred vigorously until uniform to obtain a reaction system to be crystallized (gel mixture); the reaction system to be crystallized was placed in a stainless steel crystallization kettle, sealed and dynamically crystallized in a rotary oven at 100° C. for 28 h, filtered, washed, and the filter cake was dried in an oven at 120° C. for 24 h to obtain a FAU type molecular sieve containing the metal element Zr in the framework, named Zr-D1-FAU. The physicochemical property data of the sample are shown in Table 1.
[0097] Comparative Example 7
[0098] This comparative example provides a FAU type molecular sieve, which is prepared by the following method:
[0099] The FAU molecular sieve provided in Comparative Example 6 was rinsed three times with a 1.5 mol / L ammonium sulfate solution at 85°C, and then calcined at 540°C for 2 hours. The calcined molecular sieve was rinsed three times with a 0.5 mol / L ammonium sulfate solution, and then a 0.5 mol / L manganese sulfate solution was added to the wet filter cake. After stirring evenly, it was transferred to a hydrothermal device and calcined at 600°C with water vapor for 4 hours to obtain an ultra-stable FAU molecular sieve. The sample was named Zr-D1-FAU hydrothermal. The physicochemical properties of the sample are listed in Table 1.
[0100] Example 3
[0101] This embodiment provides a strongly acidic FAU type molecular sieve, which is prepared by the following preparation method:
[0102] 9.02 g of sodium hydroxide was added to 40.52 g of distilled water, and after stirring for 30 minutes, 2.46 g of sodium aluminate and 45 g of water glass were added, and after stirring evenly, the mixture was aged at 30° C. for 6 hours to obtain a directing agent.
[0103] Add 90g of directing agent to 210g of water glass, stir for 1h, add 12.70g of sodium hydroxide, 3.46g of sodium aluminate and 140.09g of distilled water, stir for 1h, then add 136.20g of aluminum sulfate solution (Al2O3 mass concentration is 7.6wt%), stir for 1h, then add 8.1g of zirconium chloride (ZrCl4), continue stirring for 1h to obtain the reaction system to be crystallized (gel mixture). The reaction system to be crystallized is placed in a stainless steel crystallization kettle, sealed and placed in a rotary oven at 105°C for crystallization for 24 hours, filtered, washed, and the filter cake is dried in an oven at 120°C for 24 hours; the dried product is transferred to a quartz tube reactor of a rotary tube furnace, purged with high-purity nitrogen, and programmed to heat (4° / min) to 550°C, and calcined at 550°C in a nitrogen atmosphere for 4 hours to obtain a FAU type molecular sieve containing the metal element Zr in the framework (the molar ratio of ZrO2 to Al2O3 is 0.29).
[0104] Then, 8.61 g of gaseous SiCl4 was introduced into a quartz tube reactor of a rotary tube furnace containing 30 g of FAU molecular sieve containing the metal element Zr in the framework to carry out isomorphous substitution reaction at 450°C for 1 hour. Then, the product of the isomorphous substitution reaction was repeatedly washed with deionized water, filtered, dried, and calcined at 550°C in a nitrogen atmosphere for 4 hours to obtain a strongly acidic FAU molecular sieve named Zr-FAU-3-isomorphous substitution. The physicochemical properties of the sample are shown in Table 1, and the XRD spectrum is shown in Table 1. Figure 1.
[0105] Example 4
[0106] This embodiment provides a strongly acidic FAU type molecular sieve, which is prepared by the following preparation method:
[0107] 8.51 g of sodium hydroxide was added to 38.62 g of distilled water, and after stirring for 30 minutes, 2.25 g of sodium aluminate and 37.09 g of silica sol were added, and after stirring evenly, the mixture was aged at 60° C. for 2 hours to obtain a directing agent.
[0108] 45.3 g of the directing agent was added to 140.47 g of silica sol, and after stirring for 1 hour, 23.27 g of NaOH and 160 g of distilled water, 1.58 g of sodium aluminate were added, and after stirring for 1 hour, 98.72 g of aluminum sulfate solution (Al2O3 mass concentration is 7.6 wt%) was added, and after stirring for 1 hour, 2.3 g of zirconium oxychloride ZrOCl2·8H2O was added, and stirring was continued for 1 hour to obtain a reaction system to be crystallized (gel mixture); the reaction system to be crystallized was placed in a stainless steel The product was placed in a sealed crystallization kettle and subjected to dynamic crystallization in a rotary oven at 94°C for 28 hours. The product was then filtered, washed and the filter cake was dried in an oven at 120°C for 24 hours. The dried product was transferred to a quartz tube reactor of a rotary tube furnace, purged with high-purity nitrogen, and programmed to rise in temperature (4° / min) to 550°C. The product was calcined at 550°C in a nitrogen atmosphere for 4 hours to obtain a FAU type molecular sieve containing the metal element Zr in the framework (the molar ratio of ZrO2 to Al2O3 is 0.083).
[0109] Then, 8.05 g of gaseous SiCl4 was introduced into a quartz tube reactor of a rotary tube furnace containing 20 g of a FAU type molecular sieve containing the metal element Zr in the framework to carry out an isomorphous substitution reaction at 450°C for 1 hour. The product of the isomorphous substitution reaction was repeatedly washed with deionized water, filtered, dried, and calcined at 550°C in a nitrogen atmosphere for 4 hours to obtain a strongly acidic FAU type molecular sieve named Zr-FAU-4-isomorphous substitution. The physicochemical properties of the sample are shown in Table 1, and the XRD spectrum is shown in Figure 1 .
[0110] Example 5
[0111] This embodiment provides a strongly acidic FAU type molecular sieve, which is prepared by the following preparation method:
[0112] 24.02 g of sodium hydroxide was added to 40.52 g of distilled water, and after stirring for 30 minutes, 2.46 g of sodium aluminate and 25 g of water glass were added, and after stirring evenly, the mixture was aged at 40° C. for 4 hours to obtain a directing agent.
[0113] Add 50g of directing agent to 100g of water glass, stir for 1h, add 25.70g of sodium hydroxide, 3.46g of sodium aluminate and 200g of distilled water, stir for 1h, then add 136.20g of aluminum sulfate solution (Al2O3 mass concentration is 7.6wt%), stir for 1h, add 20g of zirconium chloride (ZrCl4), continue stirring for 1h to obtain the reaction system to be crystallized (gel mixture). The reaction system to be crystallized is placed in a stainless steel crystallization kettle, sealed and placed in a rotary oven at 105°C for crystallization for 24 hours, filtered, washed, and the filter cake is dried in an oven at 120°C for 24 hours; the dried product is transferred to a quartz tube reactor of a rotary tube furnace, purged with high-purity nitrogen, and programmed to heat (4° / min) to 550°C, and calcined at 550°C in a nitrogen atmosphere for 4 hours to obtain a FAU type molecular sieve containing the metal element Zr in the framework (the molar ratio of ZrO2 to Al2O3 is 0.72).
[0114] Then, 8.61 g of gaseous SiCl4 was introduced into a quartz tube reactor of a rotary tube furnace containing 20 g of FAU molecular sieve containing the metal element Zr in the framework to carry out isomorphous substitution reaction at 480°C for 1 hour. The product of the isomorphous substitution reaction was repeatedly washed with deionized water, filtered, dried, and calcined at 550°C in a nitrogen atmosphere for 4 hours to obtain a strongly acidic FAU molecular sieve named Zr-FAU-5-isomorphous substitution. The physicochemical properties of the sample are shown in Table 1, and the XRD spectrum is shown in Table 1. Figure 1 .
[0115] Table 1
[0116]
[0117]
[0118] It can be seen from Table 1 that in the process of increasing the strong acid ratio of FAU type zeolite, there is a synergistic effect between framework doping with Zr and gas-phase SiCl4 isomorphous substitution reaction. With the cooperation of framework doping with Zr and gas-phase SiCl4 isomorphous substitution reaction, a substantial increase in the framework silicon-aluminum ratio of FAU zeolite can be achieved, which is an effect that cannot be achieved by only framework doping with Zr, only SiCl4 isomorphous substitution reaction, only hydrothermal superstabilization, and both framework doping with Zr and SiCl4 isomorphous substitution reaction.
Claims
1. A method for preparing a strongly acidic FAU type molecular sieve, wherein: The method includes: A FAU type molecular sieve containing the metal element Zr in the framework is subjected to isomorphous substitution reaction with gas phase SiCl4 at a mass ratio of 0.1-20:1, and then calcined to obtain a high silicon-aluminum ratio FAU type molecular sieve; Wherein, the reaction temperature of the isomorphous substitution reaction is 200-600°C; Among them, the molar ratio of ZrO2 to Al2O3 in the FAU type molecular sieve containing the metal element Zr in the framework is 0.01-10.
0.
2. The method according to claim 1, wherein: The steps of preparing a FAU type molecular sieve containing the metal element Zr in the framework specifically include: Sodium hydroxide, an aluminum source, a silicon source and water are mixed in a molar ratio of (10-30)Na2O:Al2O3:(10-30)SiO2:(180-400)H2O, and aged at 0-80°C to obtain a directing agent; A directing agent, sodium hydroxide, a silicon source, an aluminum source, a zirconium source and water are mixed according to a molar ratio of (1-10)Na2O:Al2O3:(0.01-10.0)ZrO2:(5-20)SiO2:(120-360)H2O to obtain a reaction system to be crystallized. The reaction system to be crystallized is crystallized at 60-120°C to obtain a FAU type molecular sieve containing the metal element Zr in the framework; wherein the mass of Al2O3 provided by the directing agent accounts for 3-25% of the mass of Al2O3 in the reaction system to be crystallized.
3. The method according to claim 2, wherein: In the process of preparing the directing agent, sodium hydroxide, an aluminum source, a silicon source and water are mixed according to the molar ratio of (10-20)Na2O:Al2O3:(10-20)SiO2:(240-360)H2O.
4. The method according to claim 2, wherein: In the process of preparing the reaction system to be crystallized, the directing agent, sodium hydroxide, silicon source, aluminum source, zirconium source and water are mixed in a molar ratio of (1-5) Na2O:Al2O3:(0.01-5.0) ZrO2:(5-15) SiO2:(150-300) H2O.
5. The method according to claim 2 or 3, wherein: Aging is carried out at 10-60°C.
6. The method according to claim 2 or 4, wherein: Crystallization is carried out at 70-110°C.
7. The method according to any one of claims 2, 3 and 4, wherein: The silicon source includes at least one of ethyl silicate, water glass and silica sol; The aluminum source includes at least one of sodium metaaluminate, aluminum sulfate, aluminum isopropoxide, tert-butyl aluminum and aluminum oxide; The zirconium source includes, but is not limited to, at least one of zirconium chloride, zirconium sulfate, and zirconium oxychloride.
8. The method according to claim 1, wherein: When performing isomorphous substitution reaction, the mass ratio of the FAU type molecular sieve containing the metal element Zr in the framework to the gas phase SiCl4 is 0.5-15:
1.
9. The method according to claim 1, wherein: The reaction temperature of the isomorphous substitution reaction is 280-580°C.
10. The method according to claim 1, wherein: The molar ratio of ZrO2 to Al2O3 in the FAU type molecular sieve containing the metal element Zr in the framework is 0.05-3.
0.
11. A strongly acidic FAU type molecular sieve prepared by the method for preparing a strongly acidic FAU type molecular sieve according to any one of claims 1 to 10.
Citation Information
Patent Citations
Hydrocarbon oil desulfurization adsorbent, production and use thereof
BR112014001997A2
Mesoporous Y-type molecular sieve, preparation method and application thereof
CN110627089A
Y molecular sieve with high relative crystallinity and high silica-alumina ratio and preparation method thereof
CN114684831A
Oxide and method for production thereof
SG89056A1
Method for synthesizing a crystalline metalloaluminosilicate by direct synthesis
US20050271582A1